Creativity works! : unleash your creativity, beat the robot and work happily ever after - Luijten, Coen, ....-; van Dooren, Joris, ....- (Amsterdam : BIS Publishers, 2018)
Scientists say half the work we do could soon be done by robots and creativity is the number one skill that keeps you relevant on the job market. Even if science is wrong, it's still great fun to develop yourself creatively. In Creativity Works! the authors explain what creativity is and why we are less creative than we would like to be – blame it on our brains and the way we were treated as kids at school. In this book you'll practise basic skills to become creative and learn how a smart creative process can be designed and executed. From the formulation of a good starting question to research methods that will give you great inspiration and insights, and from smart divergent thinking to brilliant idea judgement tools: it's all in there. Furthermore, Creativity Works! gives you great instructions on successfully prototyping and selling your ideas, solutions and concepts. Let's beat the robot and work happily ever after!
Keywords: Creativiteit